The return to run process for females following a tibial bone stress injury: a scoping review - George, E.; Sheerin, K.; Reid, D. (ISBS Proceedings Archive (Michigan), 2023)
Tibial bone stress injuries (BSI) are common among female runners and have a high recurrence rate. Complete rehabilitation requires a successful return to running, but there is a lack of guidance for this. This review sought to establish the evidence supporting the return-to-running process following a tibial BSI in females. Sources were identified by searching databases using relevant terms. Study titles and abstracts were screened using inclusion criteria, and 48 articles were selected. An individualised graduated return-to-run programme should be instigated, beginning with walk-run intervals, and progressing running distance ahead of speed. The `10% rule` of graduated loading is not generalisable across all runners. Contributing factors to the initial injury should be addressed throughout the return-to-run process, including biomechanical factors and training errors.